(2/5x)-(x-3)=2

Simple and best practice solution for (2/5x)-(x-3)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2/5x)-(x-3)=2 equation:



(2/5x)-(x-3)=2
We move all terms to the left:
(2/5x)-(x-3)-(2)=0
Domain of the equation: 5x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+2/5x)-(x-3)-2=0
We get rid of parentheses
2/5x-x+3-2=0
We multiply all the terms by the denominator
-x*5x+3*5x-2*5x+2=0
Wy multiply elements
-5x^2+15x-10x+2=0
We add all the numbers together, and all the variables
-5x^2+5x+2=0
a = -5; b = 5; c = +2;
Δ = b2-4ac
Δ = 52-4·(-5)·2
Δ = 65
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-\sqrt{65}}{2*-5}=\frac{-5-\sqrt{65}}{-10} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+\sqrt{65}}{2*-5}=\frac{-5+\sqrt{65}}{-10} $

See similar equations:

| 11(4x-8)=22 | | 45=-2-13y | | -5(2x-5)=8+5-2x | | 0.33(y+5)=2y-5(y-5) | | 0.12x+0.3(x-1)=0.01(3x-4) | | -21+7w=28 | | -8(2x+1)=-6 | | 2x+6=x-4+3x | | 4x+4-6(x+1)=5x+4 | | 2x-15=-18 | | 150-10=x | | -2=-3+x/5 | | 78=4v+10 | | 8-6(6p+1)=146 | | 3n-5n+8=5-2n+3 | | 4x+8/x=2 | | 4+16x-22=1+70x+35 | | u-2.4=10.8 | | /0.75x=9 | | -2x+40=39 | | -18c=-19-19c | | 10x-x=9(x+3) | | 3/2(x+3/2)=-7/4x-19/16 | | (6x+2)+(7x+4)=45 | | 13.64=2d | | -5x+41=4 | | 12x-199=76+x | | 3x+2x+1=180 | | 0.6666666667x-3x+2.666666667=1.333333333 | | 2(4x+8)=4x+2(2x+5) | | 3u=17.49 | | -6x+13=43 |

Equations solver categories